IS POWER LISTENING TO SCIENCE? THE CASE OF ICCAT AND THE EASTERN BLUEFIN TUNA (2004-2014)1 - Gonçalves, Leandra Regina (ANPPAS - Revista Ambiente e Sociedade, 2019)
During the international tuna fishery management crisis in 2009, an epistemic community emerged at the International Commission for the Conservation of Atlantic Tunas (ICCAT) that employed collective efforts to deal with shared problems and improved the effectiveness of agreements, in terms of the recovery of Eastern Blue Fin Tuna (EBFT) stocks. This event resulted in the question: when and why does power listen to science? Through a combination of elite interviews and process tracing, this investigation analyzed the roles and influences of science and epistemic communities in the ICCAT EBFT political decisions, from 2004 to 2014. We have concluded that the EBFT case illustrates a situation where effective agreements to handle a fishery crisis in an uncertain environment were enhanced, when a transnational network of non-governmental organizations (NGOs) and the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), helped to pressure the decision-makers.

Este artículo concluye que una comunidad epistémica surgió en la CICAA y empleó esfuerzos colectivos para hacer frente a problemas compartidos y esto mejoró la eficacia del acuerdo para la recuperación de los stocks pesqueros atún azul. En ese sentido, la principal cuestión a ser respondida fue: cuando el poder oye ciencia y por qué? A través de una combinación de entrevistas con actores clave y process tracing, este trabajo analizó el papel y la influencia de la ciencia y de las comunidades epistémicas en las decisiones políticas en la CICAA para el manejo del atún azul del atlántico de 2004 a 2014 y concluyó que el caso el atún azul ilustra una situación en que en un contexto de crisis y en un ambiente lleno de incertidumbres los tomadores de decisión recurrieron a los científicos, y aceptando su asesoramiento, el manejo de la pesca fue más eficaz.

Este artigo conclui que, diante da crise internacional da gestão da pesca do atum em 2009, uma comunidade epistêmica emergiu na ICCAT e empregou esforços coletivos para lidar com problemas compartilhados e isso melhorou a eficácia do acordo em termos de recuperação dos estoques pesqueiros do atum azul. Nesse sentido, a principal questão a ser respondida foi: quando o poder ouve ciência e por quê? Através de uma combinação de entrevistas com atores-chave e process tracing, este trabalho analisou o papel e a influência da ciência e das comunidades epistêmicas nas decisões políticas na ICCAT para o manejo do atum azul do atlântico de 2004 a 2014 e concluiu que o caso do atum azul ilustra uma situação em que em um contexto de crise e em um ambiente cheio de incertezas, os tomadores de decisão recorreram aos cientistas, e aceitando seu aconselhamento, o manejo da pesca foi mais eficaz.
Keywords: ICCAT; Epistemic Communities; Eastern Bluefin Tuna; Global Fishery Governance; ICCAT; Comunidades Epistêmicas; Atum Azul; Governança pesqueira